2023
DOI: 10.3389/fnins.2023.1116111
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal dynamic functional connectivity changes correlated with non-motor symptoms of Parkinson’s disease

Abstract: BackgroundNon-motor symptoms are common in Parkinson’s disease (PD) patients, decreasing quality of life and having no specific treatments. This research investigates dynamic functional connectivity (FC) changes during PD duration and its correlations with non-motor symptoms.MethodsTwenty PD patients and 19 healthy controls (HC) from PPMI dataset were collected and used in this study. Independent component analysis (ICA) was performed to select significant components from the entire brain. Components were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 50 publications
(59 reference statements)
3
6
0
Order By: Relevance
“…We demonstrated that PD is characterized by altered temporal properties in dynamic connectivity, with a longer dwell time in segregated states and a reduced number of transitions to the more integrated states, leading to increased local segregation and reduced “crosstalk” between brain networks, particularly in PDD 6 . Other studies have now confirmed our initial findings, 44 including a 5‐year longitudinal study reporting increased functional brain disconnectivity with PD progression, that strongly correlated with global cognitive deterioration 45 …”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We demonstrated that PD is characterized by altered temporal properties in dynamic connectivity, with a longer dwell time in segregated states and a reduced number of transitions to the more integrated states, leading to increased local segregation and reduced “crosstalk” between brain networks, particularly in PDD 6 . Other studies have now confirmed our initial findings, 44 including a 5‐year longitudinal study reporting increased functional brain disconnectivity with PD progression, that strongly correlated with global cognitive deterioration 45 …”
Section: Discussionsupporting
confidence: 78%
“…6 We demonstrated that PD is characterized by altered temporal properties in dynamic connectivity, with a longer dwell time in segregated states and a reduced number of transitions to the more integrated states, leading to increased local segregation and reduced "crosstalk" between brain networks, particularly in PDD. 6 Other studies have now confirmed our initial findings, 44 including a 5-year longitudinal study reporting increased functional brain disconnectivity with PD progression, that strongly correlated with global cognitive deterioration. 45 Here, in line with these observations, PD-subgroup analyses show that the CEN and DMN neural dynamic complexity is strongly linked to cognitive status, because PDD presented a significant higher complexity in specific ICs-IC48 (CEN) and IC34 (DMN)-than PD-NC and PD-MCI, as well as in IC45 (DMN) compared to PD-NC, possibly suggesting an increased local segregation in these nodes associated with a more severe cognitive state.…”
Section: Discussionsupporting
confidence: 71%
“…Together with our previous results indicating that dynamic transitions between states of global integration and segregation are impaired in PD, these results extend the notion that PD patients may have problems transitioning specifically into a state of global integration. Interestingly, another study longitudinally investigating dFC changes in PPMI data revealed a decrease in dwell time in a state similar to the GI state and an increase in dwell time for a state corresponding to the lesser connected state(Cao et al, 2023). Their results suggest that hypocoupling worsens in the course of PD (Cao et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In PD, several recent whole-brain dFC accounts suggested the relevance of network dynamics in the clinical presentation of PD (Cao et al, 2023; Cordes et al, 2018; Díez-Cirarda et al, 2018; Fiorenzato et al, 2019; Kim et al, 2017). Importantly, these studies could show that PD-specific changes in dFC were linked to motor symptom severity (Kim et al, 2017), mild cognitive impairment (MCI) (Díez-Cirarda et al, 2018; Fiorenzato et al, 2019), PD dementia (PDD) (Fiorenzato et al, 2019), and autonomic dysfunction (Cao et al, 2023). Together, these studies emphasize that motor and cognitive impairments in PD appear to be driven by spatial and temporal alterations of large-scale network dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation